EXECUTIVE INFORMATION SYSTEM (EIS) KINERJA STUDI KASUS: CABIN BASE MAINTENANCE PT GMF AEROASIA TBK - Sudaryono Sudaryono; Harco Leslie Hendric Spits Warnars (Program Studi Sistem Informasi, Universitas Banten Jaya, 2018)
Being a company with a high level of productivity is the goal of all companies. If a company or organization has high productivity, the company or organization can be called an advanced company. PT GMF AeroAsia is one that always tries to increase its productivity. PT GMF AeroAsia is a company engaged in aircraft maintenance or known as Maintenance Repair and Overhoul (MRO). PT GMF AeroAsia always tries to improve its performance through increased manhours productivity. If the productivity productivity increases every year, the company's revenue or revenue can increase as well, thus the company will progress and develop to be equal to the world's top ten (10) Maintenance and Overhoul (MRO) companies as the vision of PT GMF AeroAsia is to become a top ten MRO in the World. Therefore, the research will be carried out by analyzing the performance through manhours productivity in every maintenance project in the base maintenance, especially in cabin base maintenance. In this study, an executive information system (EIS) in the form of a dashboard for decision makers such as managers, general managers and vice presidents will be proposed. The aim is as a source of information to identify, control performance and can help and support as a source of information for leaders in deciding wise and strategic decisions on performance, especially the performance of cabin base maintenance units at PT GMF AeroAsia